2001
DOI: 10.1074/jbc.m104738200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Rescues Retinal Neurons from Apoptosis by a Phosphatidylinositol 3-Kinase/Akt-mediated Mechanism That Reduces the Activation of Caspase-3

Abstract: The ability of insulin to protect neurons from apoptosis was examined in differentiated R28 cells, a neural cell line derived from the neonatal rat retina. Apoptosis was induced by serum deprivation, and the number of pyknotic cells was counted. p53 and Akt were examined by immunoblotting after serum deprivation and insulin treatment, and caspase-3 activation was examined by immunocytochemistry. Serum deprivation for 24 h caused ϳ20% of R28 cells to undergo apoptosis, detected by both pyknosis and activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
239
3
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(257 citation statements)
references
References 69 publications
12
239
3
3
Order By: Relevance
“…[12][13][14] In addition, apoptosis of retinal neurons induced by serum deprivation was reduced by insulin via activating the PI 3-kinase/Akt pathway. 15 Furthermore, retinal PI 3-kinase/Akt signalling pathway was activated by optic nerve clamping and had a neuroprotective effect on injured retinal ganglion cells. 16 In agreement with our results, immunoreactivity for phosphorylated Akt was detected in retinal ganglion cells in the injured retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] In addition, apoptosis of retinal neurons induced by serum deprivation was reduced by insulin via activating the PI 3-kinase/Akt pathway. 15 Furthermore, retinal PI 3-kinase/Akt signalling pathway was activated by optic nerve clamping and had a neuroprotective effect on injured retinal ganglion cells. 16 In agreement with our results, immunoreactivity for phosphorylated Akt was detected in retinal ganglion cells in the injured retina.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Several studies showed that Cox-2 functions as a survival factor by protecting cells from apoptosis. [17][18][19][20][21] Overexpression of Mcl-1, a member of the Bcl-2 family, 22 delays apoptosis by a broad array of agents.…”
mentioning
confidence: 99%
“…Insulin was a slightly more potent anti-apoptotic agent than IGF-II, an expected consequence of the fact that insulin binds to and activates IR-A with higher affinity than IGF-II . Accordingly, insulin was a more potent stimulator of IR autophosphorylation and of the IRS-1/PI3K/Akt pathway, which plays a major role in apoptosis control (Barber et al, 2001;Hiromura et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Akt mediation of IGF-1 induced survival of cerebellar neurons has been documented (Blair et al, 1999). Insulin acts as a survival factor for retinal neurons through activation of the PI3K/Akt pathway (Barber et al, 2001). Huntington's disease, a neurodegenerative disorder that manifests itself in involuntary movements, personality changes, and dementia in patients is associated with death of neurons in the striatum and alteration in the huntingtin protein.…”
Section: Discussionmentioning
confidence: 99%